The μ opiate receptor as a candidate gene for pain: Polymorphisms, variations in expression, nociception, and opiate responses - Uhl, George R. (The National Academy of Sciences, 1999)
There are differences between human individuals and between mouse strains in levels of μ opiate receptor (μOR) expression, responses to painful stimuli, and responses to opiate drugs. One of the best candidates for contributing to these differences is variation at the μOR gene locus. Support for this idea comes from analyses of the human and murine μOR genes. Assessments of individual differences in human μOR expression add further support. Studies with mice, including knockout-transgenic, quantitative trait locus, and strain-comparison studies, also strongly support the possibility that μOR gene alleles would be strong candidates for contributing to individual differences in human nociception and opiate drug responses. This paper reviews current analyses of the murine and human μOR genes, their important variants, and correlations between these variants and opiate influences on pain.